Beyond 'good' and 'bad' cyclists. On compensation effects between risk taking, safety equipment and secondary tasks. (September 2021) - Buhler, Thomas; Comby, Emeline; Vaudor, Lise; von Pape, Thilo
Abstract: Introduction: In France the number of injuries involving cyclists has risen over the last 10 years. With the widespread use of ICT devices, secondary tasks have become a major focus for transport safety research. They have also been identified as a predictor of collision. Although still scarce, this literature on cyclists' secondary tasks identifies a recurrent profile. Young cyclists are in the spotlight as they often use earbuds or headphones and combine such use with taking other major risks on the road. Despite their vulnerability, their group accounts for only 12% of severe fatalities, which is proportional to their share of the urban cyclist population. This paper explores other cyclist profiles in an attempt to understand the discrepancy between the perception of risk-prone behaviour and transport safety statistics. Methods: We seek to establish more nuanced profiles, i.e. cyclists who balance risk-taking and safety. In order to detect these profiles, we conducted 1746 observations at 14 locations in the city of Besançon (France). For each observation we considered 30 variables that provide information on the cyclist's profile, secondary tasks, risks taken, and safety equipment. Results: These observed situations show that the two well-documented profiles (i.e. 'risk-prone' or 'risk-averse') together represent only 53.84% of our observations. We identify more mitigated profiles. Primarily a large group (37.29%) consists of middle-aged and elderly cyclists who are poorly equipped, who are rarely engaged in any secondary tasks, but who take occasional risks on the road. Conclusions: Policies that aim to reduce the use of ICT devices on bike for all are necessary but not sufficient for reducing collisions. In addition to providing dedicated infrastructure, more targeted responses need to be provided to these different groups, such as focused actions on safety equipment and compliance with the traffic regulations for elderly cyclists. Highlights: Many cyclists compensate between risk-taking, safety equipment and secondary tasks. The research and operational focus on secondary tasks hides other risk profiles. Elderly cyclists are over-represented in severe collision with almost no secondary tasks. Elderly cyclist's vulnerability depends on poor equipment. Targeted policies with various profiles could be used to reduce cycling collisions.